2010
DOI: 10.1590/s1679-45082010ao1388
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods of measurement of the finger flexor muscles’ strength through dynamometry and modified manual sphygmomanometer

Abstract: The modified sphygmomanometer proved to be a reproducible technique for measuring muscle strength of the finger flexor muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
8
0
4
Order By: Relevance
“…Among the studies that evaluated the associations between the measurements obtained with the MST and portable dynamometry, which is considered the gold standard for the assessment of isometric strength 2 , significant and high correlations (0.75< r <0.98) were found only for the elbow flexors of healthy individuals using the cuff adaptation 9 , handgrip muscles of elderly individuals 25 , and healthy adults using the bag 7 , 26 and cuff 27 adaptations, as well as the anterior trunk flexors of healthy individuals and individuals with low back pain using the bag adaptation 11 . Most previous studies have investigated the correlations between the MST and portable dynamometry measures of UL muscular groups, while no study has evaluated these associations for the LL muscles or made use of the non-adapted sphygmomanometer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies that evaluated the associations between the measurements obtained with the MST and portable dynamometry, which is considered the gold standard for the assessment of isometric strength 2 , significant and high correlations (0.75< r <0.98) were found only for the elbow flexors of healthy individuals using the cuff adaptation 9 , handgrip muscles of elderly individuals 25 , and healthy adults using the bag 7 , 26 and cuff 27 adaptations, as well as the anterior trunk flexors of healthy individuals and individuals with low back pain using the bag adaptation 11 . Most previous studies have investigated the correlations between the MST and portable dynamometry measures of UL muscular groups, while no study has evaluated these associations for the LL muscles or made use of the non-adapted sphygmomanometer.…”
Section: Discussionmentioning
confidence: 99%
“…The portable dynamometer is capable of providing accurate, valid, reliable, and sensitive measurements of strength 2 - 4 ; however, its relatively high cost has hindered its use in most clinical contexts, including those in which there are insufficient financial resources. The MST provides objective, reliable, and valid measurements of strength 5 - 7 , and it has a low cost relative to the dynamometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Balogun et al (15) and recommended tables (13) for power and sample size calculations for correlation analyses, a sample of 18 subjects would be required for a power of 80%, a correlation coefficient of 0.60 and a significance level of 5%. Based on the assumption related to correlation analyses regarding sample heterogeneity, and in an attempt to obtain variability regarding strength, subjects were recruited into various age groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and > 60 years), both sexes, and various degrees of motor impairments (severe, moderate, and mild), based on the Fugl-Meyer-UL section scores (2,16,17). Therefore, the recruitment included 18 subjects in each age group with different characteristics regarding sex and motor impairments, totalling 54 subjects.…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies investigating the criterion-related validity of the MST for the assessment of UL strength (11) compared the measures provided by the modified sphygmomanometer with those obtained with the portable dynamometer, only for the elbow flexors of healthy individuals (32) and grip strength of elderly and healthy adults (15,(33)(34)(35). These studies found significant and high correlations between the measures provided by the 2 devices (0.75 ≤ r ≤ 0.96), as observed in the present study for the same muscle groups.…”
Section: Validitymentioning
confidence: 99%